Origin of low electron–hole recombination rate in metal halide perovskites. Issue 1 (4th January 2018) - Ambrosio, Francesco; Wiktor, Julia; De Angelis, Filippo; Pasquarello, Alfredo
Abstract : Isodensity representation of the hole and the electron in the excitonic state of CH3 NH3 PbI3 showing spatial separation of the polaronic charges. Abstract : To address the slow recombination of photogenerated charges in tetragonal CH3 NH3 PbI3, the evolution of extra electrons and holes is simulated through advanced ab initio molecular dynamics. We show that the localization of the charge carriers and their hopping from one polaronic state to another occur on a subpicosecond time scale. The localization, attended by weak bond contractions and elongations in the inorganic sublattice, is induced by thermal vibrations and only moderately perturbed by the disordered field generated by the organic cations. The simultaneous simulation of extra electrons and holes shows that they preferentially localize in spatially distinct regions. As determined by the overlap between the electron and hole wave functions, the probability of radiative bimolecular recombination is lowered by two orders of magnitude compared with that of optical generation. The separate polaronic localization of electrons and holes emerges as the key feature for achieving exceptional photovoltaic properties.